A Symbol of Something Greater: The Variety of Biblical Texts in Augustine’s Marriage Theology - Bowen, Meghan (Lumen et Vita, 2024)
In reflecting on marriage, theologians today tend to focus on the Creation narratives of Genesis and Paul’s Letter to the Ephesians as a basis for their articulation of the meaning of marriage. Such limitation in the Scriptural reference, though, ignores other biblical texts which may shed light on how marriage is to be lived as a Christian or how marriage is situated within the greater ecclesiological context. In examining Augustine’s writings on marriage, we discover two different but related streams of thought: the first is an exegesis on the Creation narratives which gives rise to an incidental reflection on the divine origin of marriage; and the second is a focused investigation on the function of marriage based in a much wider range of texts. In analysing Augustine’s writings on marriage, this paper demonstrates that theological reflection based in a wider range of texts can produce a richer understanding of Christian marriage.